Dynamic Stabilisation in the Treatment of Degenerative Disc Disease with Modic Changes - Olcay Eser; Cengiz Gomleksiz; Mehdi Sasani; Tunc Oktenoglu; Ahmet Levent Aydin; Yaprak Ataker; Tuncer Suzer; Ali Fahir Ozer (Advances in Orthopedics)
Objective. Posterior dynamic stabilization is an effective alternative to fusion in the treatment of chronic instability and degenerative disc disease (DDD) of the lumbar spine. This study was undertaken to investigate the efficacy of dynamic stabilization in chronic degenerative disc disease with Modic types 1 and 2. Modic types 1 and 2 degeneration can be painful. Classic approach in such cases is spine fusion. We operated 88 DDD patients with Modic types 1 and 2 via posterior dynamic stabilization. Good results were obtained after 2 years of followup. Methods. A total of 88 DDD patients with Modic types 1 and 2 were selected for this study. The patients were included in the study between 2004 and 2010. All of them were examined with lumbar anteroposterior (AP) and lateral X-rays. Lordosis of the lumbar spine, segmental lordosis, and ratio of the height of the intervertebral disc spaces (IVSs) were measured preoperatively and at 3, 12, and 24 months after surgery. Magnetic resonance imaging (MRI) analysis was carried out, and according to the data obtained, the grade of disc degeneration was classified. The quality of life and pain scores were evaluated by visual analog scale (VAS) score and Oswestry Disability Index (ODI) preoperatively and at 3, 12, and 24 months after surgery. Appropriate statistical method was chosen. Results. The mean 3- and 12-month postoperative IVS ratio was significantly greater than that of the preoperative group (P<0.001). However, the mean 1 and 2 postoperative IVS ratio was not significantly different (P>0.05). Furthermore, the mean preoperative and 1 and 2 postoperative angles of lumbar lordosis and segmental lordosis were not significantly different (P>0.05). The mean VAS score and ODI, 3, 12, and 24 months after surgery, decreased significantly, when compared with the preoperative scores in the groups (P=0.000). Conclusion. Dynamic stabilization in chronic degenerative disc disease with Modic types 1 and 2 was effective.